The motivations and challenges for academic expatriates in international branch campuses - Yao, Yao; Yang, Zhi (Frontiers in Education, 2024)
IntroductionUnderstanding the motivations and challenges experienced by academic expatriates on international branch campuses is critical for enhancing their support and management. By analyzing the motivations and challenges, the study aims to provide more understanding on management strategies of branch campuses to support expatriates in their career development and improve institutional practices.MethodsA systematic literature review was conducted, analyzing 16 studies published from 2014 onwards, using PRISMA guidelines to categorize expatriate motivations and challenges.ResultsMotivations were classified into five types: explorer, refugee, mercenary, architect, and family-oriented. Key challenges identified were rooted in balancing global integration with local responsiveness, concerning professional work, campus interactions, and career development.DiscussionThe findings highlight the need for targeted management strategies to improve the recruitment, integration, and retention of academic expatriates. The study also underscores the importance of longitudinal research to understand the long-term impacts of expatriation on individuals and institutions, contributing to the broader discourse on transnational higher education.